2009
DOI: 10.1063/1.3133803
|View full text |Cite
|
Sign up to set email alerts
|

ZnO grown by atomic layer deposition: A material for transparent electronics and organic heterojunctions

Abstract: We report on zinc oxide thin films grown by atomic layer deposition at a low temperature, which is compatible with a low thermal budget required for some novel electronic devices. By selecting appropriate precursors and process parameters, we were able to obtain films with controllable electrical parameters, from heavily n-type to the resistive ones. Optimization of the growth process together with the low temperature deposition led to ZnO thin films, in which no defect-related photoluminescence bands are obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 25 publications
9
95
0
Order By: Relevance
“…The required electron concentration in the range of 10 17 -10 18 cm -3 can be achieved [6]. Importantly, we observed that electron mobility in ZnO films grown by the ALD is relatively weakly dependent on film crystallinity [10,11].…”
Section: Zno For Transparent Electronic Devicesmentioning
confidence: 88%
See 3 more Smart Citations
“…The required electron concentration in the range of 10 17 -10 18 cm -3 can be achieved [6]. Importantly, we observed that electron mobility in ZnO films grown by the ALD is relatively weakly dependent on film crystallinity [10,11].…”
Section: Zno For Transparent Electronic Devicesmentioning
confidence: 88%
“…Use of the ALD and DEZn enabled us reduction of the growth temperature to about 100 °C, which enabled not only construction of Schottky diodes with excellent rectification rates [1,3], but also fully ZnO-based p-n diodes [6]. Moreover, low growth temperature allowed us construction of hybrid structures of the type ZnO/organic material [1,[7][8][9] with very good rectification rate and high current density, as will be discussed further on.…”
Section: Zno For 3d Memory Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…20 But unlike sol-gel deposition, ALD (like MOCVD) is limited because of the need for vacuum-processing, which restricts the size of the substrates, increases the total deposition time, and increases the processing complexity and cost. 18,21,22 Also, organometallic precursors, which are often expensive and pyrophoric, are typically used in MOCVD or ALD.…”
mentioning
confidence: 99%